Duodenal leiomyoma - Mescia, Carlos; Delgado, Bolívar; Falconi, Luis M (Cirugía del Uruguay, 1974)
There is a leiomyoma of the fourth portian of the duodenum, not diagnosed clinically or radiologicálly, which made necessary an emergency laparotomy, and a duodeno-jejunal resection, because of severe digestive bleeding. Post-operatively, a stenosis of the anastomosis made necessary a latero-lateral duodenojejunostomy, with a good long-term result. As a result of· this cáse, a search was made of the literature on duodenal leiomyoma, and the diagnostic procedures used.